An Old Man Remembering Birds - Baughman, Mike, 1937- (Book collections on Project MUSE., 2021)
"In a series of short, engaging essays, Michael Baughman reflects on his lifelong fascination with birds-on his deck in southern Oregon, at the end of a shotgun, on the beaches of Hawaii and Baja California. Birders are dedicated and passionate, and, like anglers, they all have their stories. But Baughman tells more than simple accounts of birds spotted in the field. He reflects on human-animal relations, why humans seek closeness with nature, how a dedicated birder can also be a dedicated hunter. He explores how environmental change has altered the rhythms of bird life: the ospreys that resurged after DDT was banned, the waxwings and juncos that appear rarely now as climate change takes a toll on bird populations. Baughman also describes encounters with wildfires and smoke and discusses how they shape the landscape and wildlife of contemporary Oregon. In his eighty-plus years around birds, Michael Baughman has learned one immutable lesson: as long as you remain alive and human, the closer you get to birds, and the more time you spend among them, the more you love them"--